La littérature en partage : regards croisés de voyageurs sur les bibliothèques islandaises du XIXe siècle - Mossé, Marie (Romantisme, 2017)
International audience Each travel-writer who threads the Icelandic soil in the 19th century is aware of venturing in a country which is endowed with a strong literary culture, being both the cradle of medieval sagas and a haven for ancient manuscripts. The description of Icelandic private and public libraries is therefore an invariant of travel accounts in Iceland. My paper aims to question the various meanings which is given by the traveler to this ambiguous narrative pattern. Whether the library is simply a “thing seen” that the traveler records in his log-book or it is a genuine cognitive tool able to disclose incidental truths about Iceland and Icelanders -notably the promotion of Icelandic cultural identity in the Danish colonial context, and to allow a communion between the traveler and the Icelander under the sign of literature, it also embodies the hold of fiction on the traveler, questioning the way the traveler perceives and words reality. Tout écrivain-voyageur qui foule le sol de l’Islande au xixe siècle sait qu’il s’aventure sur une terre de littérature, berceau des célèbres sagas médiévales et refuge des manuscrits anciens. C’est pourquoi la description des bibliothèques publiques et privées islandaises est un invariant du récit de voyage en Islande. Mon article entend interroger les significations dont l’écrivain-voyageur dote ce motif narratif ambigu. Simple « chose vue » qu’il consigne dans ses tablettes ou véritable outil cognitif qui révélerait des vérités obliques sur l’Islande et les Islandais – notamment la promotion de l’identité culturelle islandaise en contexte colonial danois –, et permettrait un échange authentique avec l’autre sous le signe de la littérature, la bibliothèque symbolise aussi le pouvoir de la fiction sur le voyageur, mettant en question sa perception et sa mise en discours du réel.